Bone mineral: A trojan horse for bone cancers. Efficient mitochondria targeted delivery and tumor eradication with nano hydroxyapatite containing doxorubicin. (March 2022) - Liu, Yang; Nadeem, Aftab; Sebastian, Sujeesh; Olsson, Martin A.; Wai, Sun N.; Styring, Emelie; Engellau, Jacob; Isaksson, Hanna; Tägil, Magnus; Lidgren, Lars; Raina, Deepak Bushan
Abstract: Efficient systemic pharmacological treatment of solid tumors is hampered by inadequate tumor concentration of cytostatics necessitating development of smart local drug delivery systems. To overcome this, we demonstrate that doxorubicin (DOX), a cornerstone drug used for osteosarcoma treatment, shows reversible accretion to hydroxyapatite (HA) of both nano (nHA) and micro (mHA) size. nHA particles functionalized with DOX get engulfed in the lysosome of osteosarcoma cells where the acidic microenvironment causes a disruption of the binding between DOX and HA. The released DOX then accumulates in the mitochondria causing cell starvation, reduced migration and apoptosis. The HA+DOX delivery system was also tested in-vivo on osteosarcoma bearing mice. Locally delivered DOX via the HA particles had a stronger tumor eradication effect compared to the controls as seen by PET-CT and immunohistochemical staining of proliferation and apoptosis markers. These results indicate that in addition to systemic chemotherapy, an adjuvant nHA could be used as a carrier for intracellular delivery of DOX for prevention of tumor recurrence after surgical resection in an osteosarcoma. Furthermore, we demonstrate that nHA particles are pivotal in this approach but a combination of nHA with mHA could increase the safety associated with particulate nanomaterials while maintaining similar therapeutic potential. Graphical abstract: Image 1